TEACHING METHODS OF PHYSICS IN PRE-UNIVERSITY TRAINING COURSES - Кузнєцова, Олена (SWorldJournal, 2024)
Written exams in physics in the form of external examinations, as a standardized assessment system for admission to technical higher education institutions, were officially introduced in Ukraine in 2008. Until now, entrance exams in physics were conducted